2006
DOI: 10.1007/s00417-006-0403-6
|View full text |Cite
|
Sign up to set email alerts
|

Scleral window surgery and topical mitomycin C for nanophthalmic uveal effusion complicated by renal failure: case report

Abstract: Topical MMC might relieve the blocked transscleral outflow of intraocular fluid in the small area of a sclerostomy in young patients with nanophthalmos or in patients with renal failure in whom uveal effusion occurs repeatedly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 6 publications
1
11
1
4
Order By: Relevance
“…Full-thickness cuts may be safer with the scleral punch because a rounded instrument rather than a sharp edge is presented against the choroid. We also applied MMC to inhibit further scarring, and we propose that this might be used more widely in UES, as has been recommended by others [8]. Re-exploration in this case confirmed that the previous full-thickness scleral windows had become occluded by fibrosis and scarring.…”
Section: Discussionsupporting
confidence: 80%
“…Full-thickness cuts may be safer with the scleral punch because a rounded instrument rather than a sharp edge is presented against the choroid. We also applied MMC to inhibit further scarring, and we propose that this might be used more widely in UES, as has been recommended by others [8]. Re-exploration in this case confirmed that the previous full-thickness scleral windows had become occluded by fibrosis and scarring.…”
Section: Discussionsupporting
confidence: 80%
“…MMC has been used successfully for its modulatory effects on wound healing in multiple ocular surgeries including trabeculectomy, pterygium excision, kerato-refractive surgeries, and sclerectomy for retinal detachment in nanophthalmos [1113]. In scleral resection, MMC is thought to reduce scarring of the sclerectomy bed and prevent recurrence of the exudative retinal detachment due to the regeneration of thick sclera with abnormally arranged collagen fibers [13].…”
Section: Introductionmentioning
confidence: 99%
“…In scleral resection, MMC is thought to reduce scarring of the sclerectomy bed and prevent recurrence of the exudative retinal detachment due to the regeneration of thick sclera with abnormally arranged collagen fibers [13]. Reported complications of MMC include hypotony secondary to thin cystic bleb following trabeculectomy, endophthalmitis, and corneal or scleral melting [12].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Uveal effusion syndrome has been described in association with renal failure, and the underlying mechanism may be similar to that of our hypothesis. 21 However, our subject had normal plasma albumin levels and no signs of nephropathy.…”
Section: Discussionmentioning
confidence: 59%